Variasi metode aerasi, koagulasi, dan filtrasi Dengan pasir pantai dalam meningkatkan Kualitas air sumur gali di pesisir pantai - hidayatul azizah; Abdul Khair (Politeknik Kementerian Kesehatan Banjarmasin, 2021)
Well water dug in the coastal area of Kabupaten Tanah Laut generally have qualities that do not meet the requirements. Preliminary test results show that pH and Fe has exceeded the quality standard, this study aims to determine the ability variance of Aeration, Coagulation and Filtration with beach sand media in improving quality of clean water in the coast areas in terms of turbidity, pH, and Fe parameters. The research type is experimental, and the design is Pre-test post-test with control group design. Data analysis was using Paired Sample T-Test and Wilcoxon Test. The result of measurement of dug well water in turbidity parameter of the best method was Aeration - Coagulation - Filtration with 92,47%, percentage whereas poor water treatment was using Coagulation - Filtration method with 32,56%, at pH parameter all variations of water treatment method have the same ability with 40,00% percentage, on the parameter of iron content the best method was Aeration - Coagulation - Filtration with 99.95% percentage, while the less was using Coagulation - Filtration method with 60.75% percentage. Thus it can be concluded that all methods of water treatment used to improve the quality of dug well water in the coast areas. Variance of water treatment methods can be applied to communities in coast areas as one of the alternatives in improving the quality of clean water.